Outcomes of intravascular brachytherapy for recurrent drug‐eluting in‐stent restenosis. Issue 1 (13th January 2020) - Megaly, Michael; Glogoza, Matthew; Xenogiannis, Iosif; Vemmou, Evangelia; Nikolakopoulos, Ilias; Willson, Laura; Monyak, David J.; Sullivan, Patsa; Stanberry, Larissa; Sorajja, Paul; Chavez, Ivan; Mooney, Michael; et al.
Abstract: Objectives: To examine the outcomes of vascular brachytherapy (VBT) for recurrent drug‐eluting stents (DES) in‐stent restenosis (ISR). Background: Recurrent DES‐ISR can be challenging to treat. VBT has been used with encouraging results. Methods: We report the long‐term outcomes of patients with recurrent DES‐ISR treated with VBT between January 2014 and September 2018 at a tertiary care institution. The main outcome was target lesion failure (TLF), defined as the composite of clinically driven target lesion revascularization (TLR), target lesion myocardial infarction (MI), and target lesion‐related cardiac death. Cox proportional hazards analysis was performed to identify variables associated with recurrent TLF. Results: During the study period, 116 patients (143 lesions) underwent VBT. Median follow‐up was 24.7 (14.5–35.4) months. The incidence of TLR, target‐lesion MI, and TLF was 18.9%, 5.6%, and 20.1% at 1 year, and 29.4%, 10.5%, and 32.9% at 2 years.Initial presentation with acute coronary syndrome (ACS) was independently associated with TLF (hazard ratio = 1.975, 95% CI [1.120, 3.485], p = .019). Lesions treated with intravascular ultrasound (IVUS) guidance had a lower incidence of TLR (14.3% vs. 39.6%, log‐rank p = .038), and a trend toward lower incidence of TLF (19% vs. 42.6%, log‐rank p = .086). Conclusions: VBT can improve the treatment of recurrent DES‐ISR, but TLF occurs in approximately one in three patients at 2 years. Initial presentation with ACS was associated with higher TLF and the use of IVUS with a trend for lower incidence of TLF.